Factors Influencing the Growth of Islamic Banking Industry in Sri Lanka from Employees’ Perspective - Mohammed Minhaj, Abdul Halith; Ghalia, Bouhedda (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
Abstract The growing nature of the banking industry in Sri Lanka has made a tremendous change over time to start Islamic Banking in the country. Hence, this research aimed to evaluate the perceptions of employees in the growth potential of Islamic banks and Islamic windows of conventional banks in Sri Lanka. Data were collected from 181 employees working in the Islamic banking operated in Colombo city using a structured questionnaire. The survey employs an exploratory factor analysis & inferential method to examine the respondent’s perception about the subject in Islamic Banking. The results revealed that the employees of Islamic banks perceive that Islamic banking in Sri Lanka is following Shariah and Islamic principles prescribed by the respective Shariah advisory boards. Further, they acknowledged that the objectives and practices distinguish from conventional banking to Islamic banking. The result also demonstrated that the employees hold a positive perception towards products & services, knowledge & skills gained in Islamic banking. Also, employees found a lack of knowledge regarding Islamic banking principles, products, and services within them. Further, the employee’s perception towards products and service, skills and knowledge of Islamic banking has a significant positive impact on potential growth in Sri Lanka. Also, the Islamic banking industry in Sri Lanka has tremendous potential and growth, with the majority being non-Islamic.The study suggests that it is important to address the issue of the availability of well-trained and qualified employees and to implement a comprehensive educational program to improve the understanding of Shariah among Muslims and non-Muslims who are currently catering to the market as they are from the traditional background. The above-mentioned proposal would enable the industry to develop ethically and will lay the foundation for Islamic banking in the Sri Lankan market to be sustainable.